Towards a theory of upbringing in foster care in Europe. Issue 2 (3rd March 2016) - Cameron, Claire; Reimer, Daniela; Smith, Mark
Abstract : Across Europe, foster care is the preferred intervention for children who cannot live with their birth families, yet just what states look for from foster care is rarely articulated. Its use and intended purpose can reflect not only historical peculiarities but also the nature of the welfare regime existing in a particular country. This article reports on a preliminary exploration of fostering across 11 European countries, reflecting different care and education traditions. Irrespective of variations in history and welfare ideology, and any specialist tasks, we argue that foster care, by its nature, fulfils elements of what might be described as an upbringing role on behalf of society. What is meant by upbringing and how might it be theorised? In this article we draw upon the work of the German social pedagogue, Klaus Mollenhauer, to develop a model of upbringing that might help elucidate what is involved in bringing up children, including those in state care. The idea of passing on a valued cultural heritage is central to Mollenhauer's understanding of upbringing. This happens regardless of social policy intent merely by virtue of shared daily living and the development of pedagogical relationships. We argue that a concept of upbringing might offer an integrating cross-generational theoretical framework for foster care across different welfare regimes.